2013
DOI: 10.3892/ol.2013.1611
|View full text |Cite
|
Sign up to set email alerts
|

HER2 status in advanced gastric carcinoma: A retrospective multicentric analysis from Sicily

Abstract: According to the ToGA trial, HER2 has been shown to be predictive for the success of treatment with trastuzumab in advanced gastric cancer (AGC). A number of studies have analyzed HER-2/neu overexpression in gastric carcinoma and identified the rate of HER2 positivity to be markedly varied. To date, the prevalence of HER2 overexpression in Sicilian people with AGC is unknown. Therefore, in the present study, a retrospective immunohistochemical analysis of HER2 was performed in a cohort of 304 AGC samples that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…The value of Ki-67 becomes more marked if it is seen in conjunction with Her2-neu positivity. An association between Her2-neu overexpression, Ki-67 proliferation index and a high grade and stage has been reported [27]. In our study 83% of Her2-neu positive cases showed a high Ki-67 proliferation index (Figure 1(b,c)).…”
Section: Discussionsupporting
confidence: 74%
“…The value of Ki-67 becomes more marked if it is seen in conjunction with Her2-neu positivity. An association between Her2-neu overexpression, Ki-67 proliferation index and a high grade and stage has been reported [27]. In our study 83% of Her2-neu positive cases showed a high Ki-67 proliferation index (Figure 1(b,c)).…”
Section: Discussionsupporting
confidence: 74%
“…The HER2 gene is frequently amplified and the protein overexpressed in several human epithelial malignancies, including breast, gastric, ovarian, and colon-rectal cancers [3,4,5,6,7,8,9]. In such tumors, HER2 amplification/overexpression has been linked to a poor overall outcome and a poorly differentiated phenotype [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In such tumors, HER2 amplification/overexpression has been linked to a poor overall outcome and a poorly differentiated phenotype [3,4,5,6,7]. It has also been considered a useful indicator of response to specifically targeted therapies, such as trastuzumab, that inhibit the extracellular domain of HER2 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its decreasing incidence and mortality, gastric cancer (GC) still represents the second leading cause of cancer death worldwide [13]. Approximately, 20% of cancer deaths worldwide are associated with unresolved infection or chronic inflammation; moreover, prolonged inflammation can lead to mucosal atrophy, which in some patients precedes neoplastic development [4].…”
Section: Introductionmentioning
confidence: 99%